The Effectiveness Of Sharia Arbitration In Resolving Sharia Business Disputes - Daffa Maulana Adha Herdatama; Dafa’ Alifta Akbar Susilo; Atin Meriati Isnaini; Johannes Triestanto; Iwan Rasiwan (Universitas Muhammadiyah Palu, 2026)
The rapid growth of the Islamic business sector in Indonesia necessitates dispute resolution mechanisms that are not only legally sound but also aligned with the principles of Islamic law. Sharia arbitration emerges as an alternative dispute resolution outside the court system, offering a more flexible, efficient, and substantively just process. A key institution in the implementation of sharia arbitration in Indonesia is the National Sharia Arbitration Board, which resolves disputes based on the parties’ agreements while adhering to Islamic values. This study aims to examine the effectiveness of sharia arbitration in resolving Islamic business disputes, focusing on its legal foundation, cost and time efficiency, parties’ satisfaction, and implementation challenges. The research employs a qualitative method, specifically library research, through a review of legislation, national scholarly journals, and relevant literature on arbitration and Islamic finance. The findings indicate that sharia arbitration is generally effective in resolving Islamic business disputes, particularly due to its straightforward procedures, relatively short resolution period, and ability to maintain harmonious business relationships. However, several obstacles persist, including limited public understanding of sharia arbitration, a shortage of arbitrators with specialized expertise in Islamic finance, and challenges in the enforcement of arbitration awards. To enhance its effectiveness, institutional strengthening, broader socialization, and human resource development are essential to optimize the role of sharia arbitration in Indonesia’s Islamic business sector.